Chapter Ancora su Giulio Pignatti ritrattista. Il mondo dei Grand Tourists e degli eruditi a Firenze - Leonelli, Lisa (Studi e saggi, 2020)
Giulio Pignatti or Pignatta (1679-1751), a painter from Modena who specialized in portraiture, arrived in Florence in 1705 and remained there until his death. During the fourty-six years spent in the Tuscan capital, he made contact with the last members of the Medici dynasty and with Grand Tourists as attested by the Portrait of Sir Andrew Fountaine with four friends in the Tribuna of the Uffizi, dated 1715. Pignatti's oeuvre can now be expanded by another conversation piece commissioned in 1721 by Giuseppe Aversani's pupils in the University of Pisa on the occasion of the gift of a gold medal, and by the portraits of Ludovico Tempi and Cosimo Del Sera which testifies that Pignatti worked for numerous Florentine noble families. By focusing on these paintings, the paper intends to provide a better understanding of the artist's career and patrons.